Second Five Year Plan Andhra Pradesh Review of Progress 1959-60 - Planning Commission (Planning Commission, 1960)
Andhra Pradesh was formed on 1st November 1956 by the integration of the Telangana region of the former Hyderabad State with the Andhra State. It extends over an area of 1,06,041 sq. miles forming 8.4% of the total geographical area of the Indian Union. According to 1951 Census, the State’s population was 313 lakhs and in 1959 this was estimated to have increased to 358 lakhs or 8.6% of the total estimated population of the Indian Union in that year. The population of the State is larger than that of Canada, Australia, Philippines, Netherlands, Yugoslavia, Iran, United Arab Republic, etc.
Bureau of Economics and Statistics, Government of Andhra Pradesh